2019
DOI: 10.1016/j.scitotenv.2019.01.281
|View full text |Cite
|
Sign up to set email alerts
|

Identification, origin and characteristics of bio-bead microplastics from beaches in western Europe

Abstract: Primary microplastics have been collected from 17 beaches along the Atlantic, English Channel and southern North Sea coasts of western Europe. Based on visual characteristics, these plastics were differentiated as either relatively smooth, lentil-or disc-shaped pre-production pellets (or nurdles), which were usually a few mm in diameter and were mainly white to off-white, or rougher and more irregular pellets that were slightly larger and usually black. The latter appeared to be bio-beads, or plastics that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…These bio‐beads may be similar in size to preproduction pellets (nurdles) used to manufacture plastic products. Turner et al () suggested that the release of bio‐beads contributed to the plastic litter observed on western European beaches. They further hypothesized, based on elemental analyses (e.g., Br, Sb, and Pb), that some of the bio‐beads might be derived from recycled e‐waste plastics containing toxic additives such as flame retardants.…”
Section: Microplastics In the Indoor And Terrestrial Environmentmentioning
confidence: 99%
“…These bio‐beads may be similar in size to preproduction pellets (nurdles) used to manufacture plastic products. Turner et al () suggested that the release of bio‐beads contributed to the plastic litter observed on western European beaches. They further hypothesized, based on elemental analyses (e.g., Br, Sb, and Pb), that some of the bio‐beads might be derived from recycled e‐waste plastics containing toxic additives such as flame retardants.…”
Section: Microplastics In the Indoor And Terrestrial Environmentmentioning
confidence: 99%
“…In the reviewed studies, FT-IR was performed either by measuring single particles, 16,54,59,81150 via handheld FT-IR, 137,…”
Section: Chemical Analysis Methodsmentioning
confidence: 99%
“…In this way, water reduced in organic load, ammonia, and suspended solids are obtained. Turner et al (2019) describe the use of polyethylene (made from recycled plastics from electronic industry) in local wastewater treatment plants. The PE used as a filter in this process has a high surface area where a layer of microorganisms is deposited that decomposes ammonia compounds present in the water.…”
Section: àmentioning
confidence: 99%
“…It should be mentioned that according to Turner et al (2019), these polar polymers will not only capture organic matter but also metal ions. When, as they report, these MPs containing relevant amounts of metals such as Cr, Cd, Hg, and Pb are lost from the treatment reactors, they can come into contact with natural waters becoming potential contaminants due to the leaching of the sorbed contaminants.…”
Section: àmentioning
confidence: 99%